Strong indirect herbicide effects on mycorrhizal associations through plant community shifts and secondary invasions - Lekberg, Ylva; Wagner, Viktoria; Rummel, Alexii; McLeod, Morgan; Ramsey, Philip W (Ecological applications, 2017)
Million of acres of U.S. wildlands are sprayed with herbicides to control invasive species, but relatively little is known about non-target effects of herbicide use. We combined greenhouse, field, and laboratory experiments involving the invasive forb spotted knapweed (Centaurea stoebe) and native bunchgrasses to assess direct and indirect effects of the forb-specific herbicide picloram on arbuscular mycorrhizal fungi (AMF), which are beneficial soil fungi that colonize most plants. Picloram had no effect on bunchgrass viability and their associated AMF in the greenhouse, but killed spotted knapweed and reduced AMF colonization of a subsequent host grown. Results were similar in the field where AMF abundance in bunchgrass-dominated plots was unaffected by herbicides one year after spraying based on 16:1ω5 phospholipid fatty acid (PLFA) and neutral lipid fatty acid (NLFA) concentrations. In spotted-knapweed-dominated plots, however, picloram application shifted dominance from spotted knapweed, a good AMF host, to bulbous bluegrass (Poa bulbosa), a poor AMF host. This coincided with a 63% reduction in soil 16:1ω5 NLFA concentrations but no reduction of 16:1ω5 PLFA. Because 16:1ω5 NLFA quantifies AMF storage lipids and 16:1ω5 PLFA occurs in AMF membrane lipids, we speculate that the herbicide-mediated reduction in host quality reduced fungal carbon storage, but not necessarily fungal abundance after one year in the field. Overall, in greenhouse and field experiments, AMF were only affected when picloram altered host quantity and quality. This apparent lack of direct effect was supported by our in-vitro trial where picloram applied to AMF mycelia did not reduce fungal biomass and viability. We show that the herbicide picloram can have profound, indirect effects on AMF within one year. Depending on herbicide-mediated shifts in host quality, rapid interventions may be necessary post herbicide applications to prevent loss of AMF abundance. Future research should assess consequences of these potential shifts for the restoration of native plants that differ in mycorrhizal dependency.
Keywords: Mycorrhizae; picloram; Tordon; invasion meltdown; range restoration; Centaurea; Poa bulbosa; herbicide application; 16:1ω5 lipid analysis; Herbicides; Picloram; Centaurea stoebe; plant composition; lipnicovité; arbuscular mycorrhizal fungi; pikloram; herbicidy; Montana; mykorhiza; Poaceae